1999
DOI: 10.1093/brain/122.4.779
|View full text |Cite
|
Sign up to set email alerts
|

The human amygdala plays an important role in gaze monitoring

Abstract: Social contact often initially depends on ascertaining the direction of the other person's gaze. We determined the brain areas involved in gaze monitoring by a functional neuroimaging study. Discrimination between the direction of gaze significantly activated a region in the left amygdala during eye-contact and no eye-contact tasks to the same extent. However, a region in the right amygdala was specifically activated only during the eye-contact task. Results confirm that the left amygdala plays a general role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
235
5
8

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(271 citation statements)
references
References 32 publications
20
235
5
8
Order By: Relevance
“…automatic but rather is sensitive to attention [55]. The present data also support prior suggestions that this idea that the amygdala is involved in monitoring gaze [33]. fusiform area is relatively less important for gaze percepMoreover, amygdala activity may be heightened when a tion than for facial perception in general.…”
Section: 3 Data Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…automatic but rather is sensitive to attention [55]. The present data also support prior suggestions that this idea that the amygdala is involved in monitoring gaze [33]. fusiform area is relatively less important for gaze percepMoreover, amygdala activity may be heightened when a tion than for facial perception in general.…”
Section: 3 Data Analysissupporting
confidence: 87%
“…To obtain information about specific visual analyses superior temporal sulcus (STS), and the amygdala, are taking place in STS, we designed an experiment to involved in gaze processing [1,26,32,33,46,47,54]. Gaze is determine whether differential STS activity would be usually perceived in the context of a face, and faces are elicited by repetitive eye motion vs. eye motion providing known to activate both the fusiform gyrus and the STS relevant directional information vs. directional information [1, 32,46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the right fusiform gyrus may be more responsive to whole faces and the left to face details (Rossion et al 2000). Amygdala activation may relate to aspects of emotional processing during gaze discrimination (Kawashima et al 1999), in particular to isolated eye features (Whalen et al 2004), or to attempts to search for and establish direct eye contact (Hooker et al 2003). Frontal lobe activation may relate to decision-making and aspects of attribution of mental states or theory of mind mechanisms Frith 2003, Siegal andVarley 2002) that play a role when faces are analyzed regarding information and meaning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kawashima et al (1999) reported left amygdala activation when subjects interpreted gaze direction, whereas the right amygdala was activated during eye-to-eye contact [201]. In another study, the eye region was sufficient to elicit amygdala responses during fMRI [202].…”
Section: The Neural Substrates For Recognition Of Emotion Expressionsmentioning
confidence: 96%